The role of stem cells in dentistry: Biological solutions to biological problems - Namdeo Prabhu; Rakhi Issrani (Wolters Kluwer Medknow Publications, 2014)
Advances in the field of dentistry in the last millennium and in the present decade have brought about revolutionary changes in the way we understand and treat diseases. The stem cells are one of the most favorable areas of biology. The breakthrough in stem cell research holds significant promise for clinical application in human patients to regenerate human cells, which are damaged due to illness, developmental defects, and accidents. This article takes you on a sojourn of the stem cells, their characteristics, sources, their potential applications and possible barriers of its application along with the overview of where dentistry stands in this field.